Altered Preoperative Nutritional Status in Colorectal Cancer: A Not So Infrequent Issue. (7th November 2020) - Páramo-Zunzunegui, Javier; Ramos-Carrasco, Araceli; Alonso-García, Marcos; Cuberes-Montserrat, Rosa; Rodríguez-Caravaca, Gil; Durán-Poveda, Manuel
Abstract : Introduction . Malnutrition and weight loss in cancer patients is a common problem that affects the prognosis of the disease. In the case of CRC, malnutrition rates range between 30 and 60%. Objectives . Description of the preoperative nutritional status of patients diagnosed with colorectal neoplasia who will undergo surgery. Materials and Methods . A prospective observational study is performed. Results . Of 234 patients studied, we observed that 139 (59%) had some degree of nutritional risk. Of all of them, 44.9% ( N = 47) had 1-2 points according to MUST and 25% ( N = 27) had more than 2 points. No differences were found when studying nutritional risk according to the location of the neoplasm. It was observed that 2.15% of the patients were underweight, 51% overweight, and 23% obese. 19.4% of patients lost less than 5 kg in the 3–6 months prior to diagnosis, 20.7% lost between 5 and 10 kg, and 2.1% lost more than 10 kg. In asymptomatic patients, the weight loss was lower than in symptomatic patients, loss <5 kg, 8.2% vs. 22.8%, and loss 5–10 kg, 16.2% vs. 29.3%, with a value of p = 0.016 . 5% ( N = 7) of the patients had hypoalbuminemia record. 16.5% ( N = 23) had some degree of prealbumin deficiency and 20.9% ( N = 29) of hypoproteinemia. Symptomatic patients had more frequent analytical alterations, 1-2 altered parameters in 48.8% ( N = 20) of asymptomatic vs. 61.2% ( N = 22) in the symptomatic, p = 0.049 .